Rules of civility eaudiobook A novel. - Towles, Amor (Penguin Audio, 2011)
A sophisticated and entertaining debut novel about an irresistible young woman with an uncommon sense of purpose. Set in New York City in 1938, Rules of Civility tells the story of a watershed year in the life of an uncompromising twenty-five-year- old named Katey Kontent. Armed with little more than a formidable intellect, a bracing wit, and her own brand of cool nerve, Katey embarks on a journey from a Wall Street secretarial pool through the upper echelons of New York society in search of a brighter future. The story opens on New Year's Eve in a Greenwich Village jazz bar, where Katey and her boardinghouse roommate Eve happen to meet Tinker Grey, a handsome banker with royal blue eyes and a ready smile. This chance encounter and its startling consequences cast Katey off her current course, but end up providing her unexpected access to the rarified offices of Conde Nast and a glittering new social circle. Befriended in turn by a shy, principled multimillionaire, an Upper East Side ne'er-do-well, and a single-minded widow who is ahead of her times, Katey has the chance to experience first hand the poise secured by wealth and station, but also the aspirations, envy, disloyalty, and desires that reside just below the surface. Even as she waits for circumstances to bring Tinker back into her orbit, she will learn how individual choices become the means by which life crystallizes loss. Elegant and captivating, Rules of Civility turns a Jamesian eye on how spur of the moment decisions define life for decades to come. A love letter to a great American city at the end of the Depression, readers will quickly fall under its spell of crisp writing, sparkling atmosphere and breathtaking revelations, as Towles evokes the ghosts of Fitzgerald, Capote, and McCarthy.